2013
DOI: 10.32674/jis.v3i1.522
|View full text |Cite
|
Sign up to set email alerts
|

“He’s an idiot!” Experiences of International Students in the United States

Abstract: Kim, a doctoral student from South Korea, went to a grocery store after being in the U.S. for only one week. When he got to a counter to pay for the items that he picked up, a clerk asked if Kim wanted cash back when he paid with his debit card. Since there was no cash back system in grocery markets in his home country, Kim did not understand right away what the clerk meant. Kim seemed to be puzzled and responded, “Yes, I want cash [back]” but changed his answer in a few seconds, “No, no, no. [I] don’t need [i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Research has shown international students from Western and English‐speaking countries have reported little or less experience of discrimination and violation compared to those from other regions (Hanassab, 2006; Lee & Rice, 2007). In addition, English fluency and foreign accents, which often intersect with racial and ethnic backgrounds, can also influence how international students are treated (Bernstein et al., 2011; Ee, 2019).…”
Section: Spanning Systems Modelmentioning
confidence: 99%
“…Research has shown international students from Western and English‐speaking countries have reported little or less experience of discrimination and violation compared to those from other regions (Hanassab, 2006; Lee & Rice, 2007). In addition, English fluency and foreign accents, which often intersect with racial and ethnic backgrounds, can also influence how international students are treated (Bernstein et al., 2011; Ee, 2019).…”
Section: Spanning Systems Modelmentioning
confidence: 99%
“…Research has also looked at adaptation difficulty and its impact on emotional well-being in the form of feelings of loss and loneliness (Patron, 2014). Furthermore, Ee (2013) highlighted the experiences of international students with microaggressions, physical and sexual assaults, race and language related assaults. In a qualitative study utilizing group interviews of six international students focused on issues of international student retention (Bista & Foster, 2011).…”
Section: Social and Emotional Risk Factorsmentioning
confidence: 99%
“…Thus, social and emotional safety research indicates that internationals, who are from predominantly non-White or non-English speaking regions of the world, often struggle with adjustment, experience discrimination, macro and microaggressions, and building social connections (Contreras-Aguirre & Gonzalez, 2017;Ee, 2013;Zhang & Goodman, 2011). These issues often resulted in feelings of isolation, loneliness, depression (Li et al, 2014;Patron, 2014).…”
Section: Social and Emotional Risk Factorsmentioning
confidence: 99%
“…Studies have shown that international students from non-Western and non-English-speaking countries experience greater levels of discrimination and are more likely to be regarded by peers as “others” compared to international students from Western and English-speaking countries (Ee, 2013). Empirical investigations have documented that experiencing discrimination adversely affects self-esteem and overall satisfaction with life in the U.S. among international students and leads to higher psychological distress (Lee & Rice, 2007; Wang et al, 2013).…”
Section: Discrimination Against Asian International Students From An ...mentioning
confidence: 99%